2016
DOI: 10.1111/fme.12181
|View full text |Cite
|
Sign up to set email alerts
|

Investigating patterns of straying and mixed stock exploitation of sea trout, Salmo trutta, in rivers sharing an estuary in south‐west England

Abstract: Fisheries Management and EcologyFor effective management, information on the stock composition of a fishery is essential. 5Here, we highlight the utility of a resident trout microsatellite baseline to determine the 6 origins of sea trout entering the Rivers Tamar, Tavy and Lynher in southwest England -all 7 share a common estuary and have major runs of sea trout. There is a high degree of 8 geographical structuring of the genetic variation in the baseline rivers. Testing with simulated 9 and real datasets show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 67 publications
4
59
0
Order By: Relevance
“…Instead, they appeared to stay the winter at sea, in estuaries or in some cases in another river according to recaptures of tagged fish, as also reported from some other studies (King et al, 2016;Knutsen et al, 2004;Olsen et al, 2006). Instead, they appeared to stay the winter at sea, in estuaries or in some cases in another river according to recaptures of tagged fish, as also reported from some other studies (King et al, 2016;Knutsen et al, 2004;Olsen et al, 2006).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Instead, they appeared to stay the winter at sea, in estuaries or in some cases in another river according to recaptures of tagged fish, as also reported from some other studies (King et al, 2016;Knutsen et al, 2004;Olsen et al, 2006). Instead, they appeared to stay the winter at sea, in estuaries or in some cases in another river according to recaptures of tagged fish, as also reported from some other studies (King et al, 2016;Knutsen et al, 2004;Olsen et al, 2006).…”
Section: Discussionsupporting
confidence: 77%
“…However, runs of that size appear adequate to maintain viable populations of anadromous brown trout, as reported by Thomson and Lyndon (2018) from the Orkney, UK. Anadromous trout sometimes visit lower parts of rivers other than their home stream (Euzenat, 1999;Jensen et al, 2015;King et al, 2016;Masson et al, 2018;Solomon, 2006). The effective straying rate, however, may be low as immature first-time migrants tend to enter other streams more often than the mature veteran migrants do.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within regions displaying a mosaic of small and large populations, straying and the degree of genetic connectivity may be skewed, whereby large populations can act as net‐exporters of strayers to smaller neighboring wild populations (Hansen, Skaala, Jensen, Bekkevold, & Mensberg, ). Straying of wild fish between rivers (Stabell, ) also varies in time and space for Atlantic salmon (Jonsson & Jonsson, ; Jonsson et al., ; Pedersen et al., ; Skilbrei & Holm, ) and other salmonids (Bett, Hinch, Burnett, Donaldson, & Naman, ; Ford, Murdoch, & Hughes, ; King, Hillman, Elsmere, Stockley, & Stevens, ). Recent experimental work has also indicated that introgression of domesticated salmon may increase straying rates in impacted wild Atlantic salmon populations (Jonsson & Jonsson, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, interrupted or imperfect imprinting during rearing or juvenile migration can increase straying rates (Keefer & Caudill, ). There also appear to be genetically based differences across populations in straying rates and distances (Jonsson & Jonsson, , ; Keefer & Caudill, ; King, Hillman, Elsmere, Stockley, & Stevens, ), with selection thought to favor higher straying when habitat quality or quantity fluctuates unpredictably through time (Hendry et al, ; Quinn & Tallman, ).…”
Section: Introductionmentioning
confidence: 99%